Phonon-limited mobility and quantum transport in fluorinated diamane MOSFETs from the first-principles calculations. (February 2023) - Dong, Linpeng; Li, Penghui; Li, Chong; Roqan, Iman S.; Peng, Bo; Xin, Bin; Liu, Weiguo
Abstract: Two-dimensional diamane with outstanding properties is promising for advanced nanodevice applications, whereas a comprehensive understanding of phonon-limited mobility as well as the prediction of device performance limit is still lacking. Here we report on phonon-limited mobility simulation in fluorinated diamane monolayer using first-principles calculations, with consideration of both elastic and inelastic phonon scattering processes based on Boltzmann transport equation. We construct sub-7 nm fluorinated diamane metal-oxide-semiconductor field-effect transistors (MOSFET) to investigate their quantum transport properties by first-principles calculations based on density functional theory coupling with the non-equilibrium Green's function formalism. Our findings show that fluorinated diamane mobility is concentration-dependent, with the electron and hole mobility reaching as high as 4390 and 10100 cm 2 V −1 s −1, respectively, at the 10 14 cm −2 carrier concentration. Our simulations reveal that the key figures of merits (FOMs) of fluorinated diamane MOSFETs are benchmarked against the International Technology Roadmap for Semiconductors (ITRS) standards for high-performance (HP) and low-power (LP) applications, showing superior potential compared to the most reported 2D materials. The simulated results demonstrate that the on-current, delay time, and power-delay product meet the ITRS requirements for HP and LP applications, including devices constructed with nano-scale channel length (≥3 and 5 nm) respectively. Finally, we show that the performance of a 32-bit ALU based on fluorinated diamane MOSFETs is comparable with emerging beyond-CMOS devices. Thus, our results shed light on the electronic properties of fluorinated diamane, making it superior to serve as a channel material in the post-silicon era. Graphical abstract: Image 1 Highlights: The phonon-limited mobility of monolayer fluorinated diamane is calculated. The electron/hole mobility is 4390/10100 cm 2 V −1 s −1 at concentration of 10 14 cm −2 . Quantum transport properties of fluorinated diamane MOSFETs are simulated. The FOMs indicates fluorinated diamane is suitable for sub-5nm applications.